The test of time: A 21st Century Commentary on Introduction to informetrics - González-Salmón, Elvira (Anuario ThinkEPI, 2023)
Informetrics has changed enormously since 1990, when Leo Egghe and Ronald Rousseau first published Introduction to informetrics: Quantitative methods in library, documentation and information science. In this note we revisit this informetrics classic, with an emphasis on analysing the contrasts and continuities found between the first approach to the term proposed by these authors and the reality of this field of research in 2023.
Keywords: Informetrics; Bibliometrics; Documentation; Library science